ANALISIS BAURAN PEMASARAN (4P) TERHADAP KEPUTUSAN PEMBELIAN VAKSIN TERNAK MEREK MEDIVAC AI DI KOTA KEDIRI - Suhendro, Suhendro; Hakimah, Ema Nurzainul; Sardanto, Rino (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
The background of this research is that pusrchasing decisions need to be analyzed using the 4P marketing mix Product, Promotion, Price, Distribution. The 4P marketing mix Analysis is neede be the company to to find out the factors behind consumers in making decisions to purchase the Medivac AI Vaccine PT Medion Kediri. This study aims to determine the product marketing mix, promotion, price, and distribution have a significant effect on purchasing decisions for Medivac AI livestock vaccines in the city of Kediri. This study uses a quantitative approach with stastictichal methods (tes equipment) to calculate datathat will produce a conclusion. The sample from this study were regular customers who had used Medivac AI vaccine products in the city of Kediri and were analyzed quatitatively using tha classical assumption test an using multiple linier regression with SPSS for Windows sofware version 22. The conclucions of study are product, price, and variable distribution partially has a significant effect on purchasing decisions, while promotion partially does not have a sinificant effect of purchasing decision. The novelty of research is that in the field of animal husbandy pharmaceutical promotion programs carried out by companies are not always directlt proportional to ha significance of the purchasing decisions, but can also be influenced, by others factors. Keywords: Product, Promotion, Price, Distribution, Purchase Decision